The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1186/s12875-015-0363-1
|View full text |Cite
|
Sign up to set email alerts
|

Retaining the general practitioner workforce in England: what matters to GPs? A cross-sectional study

Abstract: BackgroundThe general practice (GP) workforce in England is in crisis, reflected in increasing rates of early retirement and intentions to reduce hours of working. This study aimed to investigate underlying factors and how these might be mitigated.MethodsGPs in central England were invited to participate in an on-line survey exploring career plans and views and experiences of work-related pressures. Quantitative data were analysed using logistic regression analysis and principal components analysis. Qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 11 publications
2
60
0
Order By: Relevance
“…Similar themes to those in the present study arose, including increased patient expectations, recruitment and retention difficulties, burgeoning administration and bureaucracy, transfer of work from secondary care, and the introduction of 7-day working. 21 The latter concern was raised by some GPs in the present study, perhaps because the '7-day NHS' formed part of the government's election campaign shortly before the interviews were conducted. 22 A recent mixed methods study exploring why so many GPs in England leave practice before the age of 50 also found that increased workloaddue in part to increased bureaucracy, the shift of work from secondary care to primary care, a change in patient demands, and time pressures -is a major contributor.…”
Section: Comparison With Existing Literaturementioning
confidence: 88%
“…Similar themes to those in the present study arose, including increased patient expectations, recruitment and retention difficulties, burgeoning administration and bureaucracy, transfer of work from secondary care, and the introduction of 7-day working. 21 The latter concern was raised by some GPs in the present study, perhaps because the '7-day NHS' formed part of the government's election campaign shortly before the interviews were conducted. 22 A recent mixed methods study exploring why so many GPs in England leave practice before the age of 50 also found that increased workloaddue in part to increased bureaucracy, the shift of work from secondary care to primary care, a change in patient demands, and time pressures -is a major contributor.…”
Section: Comparison With Existing Literaturementioning
confidence: 88%
“…13 There is evidence to show that increased work stress and work intensity leads GPs under 'high strain' to report higher levels of anxiety, depression, and dissatisfaction than GPs under 'low strain', and that the health impacts of stress continued outside of work, which in turn could increase job dissatisfaction and intention to quit the profession. 43,44 Job satisfaction is also influenced by expectations about future events. 45 If doctors perceive that their workload will not reduce, and that demands will always increase, it is likely that they will feel more overwhelmed and less satisfied with their job, and thus more likely to quit.…”
Section: Retention Of Gpsmentioning
confidence: 99%
“…Given the administrative burden associated with primary care in the UK, [16] there is potential for some of these difficulties to have particular significance in the context of GP training. As with dyslexic adults in other occupational settings, [5] doctors have developed a sophisticated array of coping strategies to mitigate their difficulties.…”
Section: Support Strategiesmentioning
confidence: 99%